Perancangan Web Service REST API Menggunakan PHP dan Framework Laravel di Tenta Tour Salatiga - Gowell, Kent; Suprihadi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Growth in Indonesia’s tourism is increasing rapidly with over hundred thousands of yearly visitors. Travel agencies like Tenta tour provides travel and tourism planning services for customers, offering easy process and packages suited for any needs. Conventional methods used for planning tour plans are deemed inefficient and ineffective. To solve problems commonly found, a web service is designed to provide data transfer and management. The system is developed with a prototyping model until requirements are met, followed by system testing to ensure stable and fast performance. The research produced an integrated system by utilizing REST API web service and offering interoperability across systems. The system provides information on available travel packages and offers reservation and customization features. Results from performance testing show the capabilities of implemented web service design in managing requests and responses. The system provides responsive and easy data transfer and management.